2011
DOI: 10.1039/c0cp02914a
|View full text |Cite
|
Sign up to set email alerts
|

Unique interplay between electronic states and dihedral angle for the molecular rotor diphenyldiacetylene

Abstract: A new analysis of the optical properties of the molecular rotor 1,4-diphenyl-1,3-butadiyne (diphenyl-diacetylene, DPDA) is presented, taking account of the conformational dynamics. The absorption spectra are interpreted in terms of simultaneous contributions from planar as well as non-planar rotamers, characterized by a temperature dependent equilibrium distribution. The investigation is based on IR Linear Dichroism and UV Synchrotron Radiation Linear Dichroism (SRLD) spectroscopy on oriented samples in stretc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 51 publications
3
41
0
Order By: Relevance
“…60 Calculations have indicated that the barrier for diphenyldiacetylene (DPDA, Ph-C≡C-C≡C-Ph) is around 1.1 kJ mol −1 (PBE1PBE/6-31+G*//6-31G* and B3LYP/6-31+G**). 61,62 1,4-Bis(phenylethynyl)benzene (Ph-C≡C-C 6 H 4 -C≡C-Ph) has an experimental barrier of 2.75 kJ mol −1 , similar to that for tolane, but DFT (B3LYP/6-31G**) dramatically overestimates the barrier at 8.75 kJ mol −1 . 63 To ensure comparability of computational results, we have calculated the torsion barrier of tolane and DPDA at the B3LYP/6-31G* level of theory, by performing constrained geometry optimisations of planar and perpendicular conformers.…”
Section: Evidence For Enhanced Conjugation In the Planar Conformer From C≡c Bond Length And Vibrational Frequenciesmentioning
confidence: 94%
“…60 Calculations have indicated that the barrier for diphenyldiacetylene (DPDA, Ph-C≡C-C≡C-Ph) is around 1.1 kJ mol −1 (PBE1PBE/6-31+G*//6-31G* and B3LYP/6-31+G**). 61,62 1,4-Bis(phenylethynyl)benzene (Ph-C≡C-C 6 H 4 -C≡C-Ph) has an experimental barrier of 2.75 kJ mol −1 , similar to that for tolane, but DFT (B3LYP/6-31G**) dramatically overestimates the barrier at 8.75 kJ mol −1 . 63 To ensure comparability of computational results, we have calculated the torsion barrier of tolane and DPDA at the B3LYP/6-31G* level of theory, by performing constrained geometry optimisations of planar and perpendicular conformers.…”
Section: Evidence For Enhanced Conjugation In the Planar Conformer From C≡c Bond Length And Vibrational Frequenciesmentioning
confidence: 94%
“…SRLD spectra were measured at room temperature as previously described [29][30][31][32][33] on the CD1 beamline [27,28] at the storage ring ASTRID at the Centre for Storage Ring Facilities (ISA). Two absorbance curves were recorded with the electric vector of the sample beam parallel and perpendicular to the stretching direction of the PE polymer.…”
Section: Linear Dichroism (Ld) Spectroscopymentioning
confidence: 99%
“…Secondly, the use of synchrotron radiation [27,28] enables a substantial expansion of the investigated spectral range, compared with the use of a traditional light source [29][30][31][32][33]. In the present investigation, the measurement is thus extended into the vacuum UV, covering the region up to 58000 cm -1 (170 nm).…”
Section: Introductionmentioning
confidence: 99%
“…2.46 kJmol −1 ),, and 3) the sp ‐ sp bond between two ethynyl groups ( ca . 1.12 kJmol −1 ) ,. As a result of the relatively low rotation barriers of the sp ‐ sp 2 bonds and, particularly, the sp ‐ sp diacetylene bond, compound 2 exchanges dynamically in solution between 4 main types of similarly populated π‐conjugated conformations, obtained by fast 90° rotation of any of these bonds.…”
Section: Figurementioning
confidence: 99%